Clinical profile and outcome of H1N1 influenza in children- a tertiary care experience - Pushpalatha, K; Sushma, C; Udayakumar, S; Mridula, A M; Archana, V (Indian Journal of Child Health, 2016)
Background: H1N1 influenza pandemic began in Mexico in 2009 and soon spread to the other parts of the globe. The 2009 H1N1 virus contained a unique combination of gene segments that had not previously been identified in humans or animals. Objective: To study the clinical and epidemiological profile and outcome of H1N1 influenza among children admitted to pediatric ward and intensive care unit. Materials and Methods: Prospective data of 82 children with suspected influenza illness were collected, and throat swabs sentfor reverse transcription polymerase chain reaction testing for H1N1. Epidemiological characteristics were analyzed in terms of clinical presentation and outcome. Results: Of the total 82 children with suspected influenza, majority (56.09%) were males, and majority (51.2%) were in the age group of 1-5 years. Throat swab was positive for H1N1 isolate in 22 (26.8%) cases. Clinically, all of them had flu-like illness. All 22 (100%) confirmed H1N1 cases had fever, 21 (95.4%) had cough, 18 (81.8%) had breathlessness, and 15 (68.1%)had running nose. 18 (81.8%) had chest X-ray abnormalities. 1 (4.5%) required mechanical ventilation and 1 (4.5%) succumbed to the illness. Conclusion: Fever, cough, breathlessness, and chest X-ray abnormalities were the most common presentation. A high index of suspicion of swine flu, during epidemics, and early treatment will lessen the mortality rates.